A bibliometric analysis of research on entrepreneurial intentions from 2000 to 2018. Issue 2 (16th December 2019) - Dolhey, Shivam
Abstract : Purpose: The purpose of this study is to provide a bibliometric analysis of the research on entrepreneurial intentions. A total of 1, 393 papers published from the year 2000 to 2018 are analysed. The study attempts to identify the significant journals in this area, years with the maximum publication, most cited papers, important authors and most prolific countries and institutions. Then, the co-authorship network map, inter-country co-authorship network map and keyword co-occurrences network maps are provided. Design/methodology/approach: The Scopus database was used for analysing the large data about various papers included in this study. Then, the VOSviewer software was used for creating a co-authorship network map, inter-country co-authorship network map and keywords co-occurrences network maps. Findings: The results of this study indicate that in the year 2017, the maximum papers have been published, the most significant journal is International Journal of Entrepreneurship and Small Business and the most cited paper is about competing models of entrepreneurial intentions. Furthermore, the most prominent author is Francisco Linan, and the most prolific country and institution are the USA and the University of Seville (Spain), respectively. Originality/value: This study contributes to the existing literature on entrepreneurial intentions. A much comprehensive and reliable picture of this area is provided using the bibliometric techniques. The results can help in guiding the authors interested in conducting future research on this topic.